English Education Master Students' Perceptions on Their Agency as Future EFL Teachers - Kristian Florensio Wijaya (Journal of Foreign Language Teaching and Learning, 2021)
This study investigated English Education Master Students’ perceptions of their agency as future EFL teachers. The underlying concern for conducting this study is a shortage of future EFL teachers’ professional development literature exploring the significance of promoting agency in varied second language classroom contexts. The narrative inquiry approach was employed to obtain more overarching depictions about the apparent stories told by the research participants to fulfil this central research objectivity. Ten open-ended written narrative inquiries were harnessed to shed more enlightenment for future EFL teachers’ professional development with the support of robust agency establishment. This set of narrative inquiry questions heed more profound attention to dig out graduate EFL students’ perceptions of their agency as prospective second language educators. The obtained findings overtly revealed that future EFL teachers could elevate their agency and promote holistic second language learning enterprises while their school institutions imparted continuous mutual supports. Eventually, the findings will shed more enlightenment for ELT experts, practitioners, and policymakers to design more unrestricted educational regulations. They supportively substantiate future EFL teachers' agency growth, particularly in Indonesia's EFL learning contexts, emphasizing the text-based learning achievements.